Measuring the Economic Value of a Marine Protection Program against the Introduction of Non-Indigenous Species in the Netherlands - Paulo A.L.D. Nunes; Jeroen C.J.M. van den Bergh (Tinbergen Institute, 2002)
Harmful algal bIoom species are the cause of important damages to marine living resources and human beings. These marine species are primarily introduced in North-European waters through ballast water, i.e. water trans-ported across the oceans so as to keep a vessel in balance. Port authorities can impose standards on ballast water treatment, which are associated with costs. This, in turn, leads to the question which benefits are associated with the commitment of such standards. Monetary valu-ation can provide information on this. This article reports a monetary valuation study of a marine protection pro-gram. The program focuses on the prevention of harmful algal bIoom species along the coastline of the Nether-lands. It entails the construction of a ballast water dis-posal treatment in the Rotterdam harbor, and the imple-mentation of a monitoring program of the water quality in the open sea along the North-Holland beaches. The valuation survey is based on a questionnaire undertaken at Zandvoort, a famous Dutch beach resort. Since the economic value of the marine protection program included non-market benefits associated with beach recreation, human health and marine ecosystem impacts, both contingent valuation and travel cost methods are used.
Keywords: C24; C25; Q25; Q26; 330; Contingent valuation; Harmful algal blooms; Marine management; Monetary valuation; Travel cost method.; Meeresverschmutzung; Naturschutz; Kosten-Nutzen-Analyse; Willingness to pay; Reisekostenansatz; Niederlande